PENGARUH SISTEM TANAM KONVENSIONAL DAN RATUN TERHADAP KEBERADAAN HAMA UTAMA, PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) - Khairun Nisa Saputri Dewi; Saifuddin Hasjim (Universitas Trilogi, 2021)
Rice is an important commodity in Indonesia because it is the main foodstuffs consumed daily by people in Indonesia. Farmers often fail in cultivation of rice plant thereby affecting availability of foodstuffs. One of the causes of the occurrence of the failure of the rice production and a decrease in cultivation, namely the existence of pests that attack the land planting. Influential factors to the existence of pests one is cropping system. This research was conducted to find out the where abouts of the pests on the Ratoon and conventional cropping systems. Observations on this research use the dwarf in the random sampling on the diagonal line with Conventional and Ratoon cropping systems. Vareitas used was Sertani 13 with planting distance 25 x 25 acres 50 m2 x 20 m2. The parameters of the observations made are high pest populations of plants, pests, the intensity, the number of saplings and results of production. The data obtained will be analysed in the descriptive is with the compare between Conventional cropping systems and systems of cultivation Ratoon. The results showed that conventional cropping systems and has a good influence ratun towards growth and pest populations while having less clout both to the production of rice. Keywords : Conventional, Ratoon, Rice pests.